2011
DOI: 10.1002/tox.20717
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic methylation metabolism and liver injury of acute promyelocytic leukemia patients undergoing arsenic trioxide treatment

Abstract: Although arsenic is effective in the treatment of acute promyelocytic leukemia (APL), as a well-known environmental toxicant, the side effects of arsenic treatment and arsenic methylation metabolism of the patients are rarely reported. In this manuscript, we investigated 23 APL patients treated with 10 mg arsenic trioxide daily, detected the arsenic metabolites in urine samples collected on the 0, 10th, and 20th day of arsenic treatment. At the same time, liver function and blood routine examination were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Our findings from Chile suggest that high doses sometimes used in treatment of promyelocytic leukemia would not be needed. Intravenous doses of 10 mg of arsenic trioxide per day for leukemia patients result in urine total arsenic concentrations of 4,000 to 5,000 μg/g creatinine in urine ( Wang et al, 2013 ), whereas drinking water arsenic concentrations of about 600 μg/L in our study in Chile resulted in urine total arsenic concentrations of about 600 μg/g of creatinine ( Biggs et al, 1997 ). Importantly, this comparison suggests that inorganic arsenic in drinking water in the treatment of breast cancer could be at much lower doses than those given with intravenous therapy of promyelocytic leukemia.…”
Section: Discussionmentioning
confidence: 54%
“…Our findings from Chile suggest that high doses sometimes used in treatment of promyelocytic leukemia would not be needed. Intravenous doses of 10 mg of arsenic trioxide per day for leukemia patients result in urine total arsenic concentrations of 4,000 to 5,000 μg/g creatinine in urine ( Wang et al, 2013 ), whereas drinking water arsenic concentrations of about 600 μg/L in our study in Chile resulted in urine total arsenic concentrations of about 600 μg/g of creatinine ( Biggs et al, 1997 ). Importantly, this comparison suggests that inorganic arsenic in drinking water in the treatment of breast cancer could be at much lower doses than those given with intravenous therapy of promyelocytic leukemia.…”
Section: Discussionmentioning
confidence: 54%
“…PMI: primary methylation index; SMI: secondary methylation index a All the other SNPs of AS3MT showed no significant influence on arsenic metabolism, therefore only A9749G and A27215G are presented reactive oxygen species and lead to cytochrome C leakage, DNA damage and apoptosis [25]. More importantly, acute liver dysfunction might lead to a decrease in the capacity of arsenic methylation [26], thus relatively higher iAs III % in the urine, hair and nails would last for a long time as shown in our study. Incomplete methylation of iAs III would cause tissue and organ damage under oxidative stress, including chronic liver dysfunction and hepatic steatosis as presented in our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the conventional all-trans retinoic acid and chemotherapeutic drugs, ATO not only can induce CR consistently though as a single agent but also showed promising anticancer activities on other malignancies (Emadi and Gore, 2010;Mathews et al, 2010;Khairul et al, 2017). However, long-term and high-dose medication of ATO will inevitably cause bioaccumulation of arsenic metabolites, which are associated with adverse effects (Wang et al, 2013;Xiang et al, 2019). Previous studies have suggested that appropriate dosage can reduce the incidence of potential adverse effects (Lo-Coco et al, 2013;Gill et al, 2018;Kumana et al, 2020), and proposed several possible mechanisms of organ toxicity, including the promotion of oxidative damage, disturbance of ion channel balance, alteration of DNA methylation, and so on (Alamolhodaei et al, 2015;Hu et al, 2018;Chang and Singh, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Trivalent arsenicals show high binding affinity to thiol groups of free cysteine residues, leading to structural modifications of proteins as well as enzyme inhibition (Shen et al, 2013;Soria et al, 2017). Comparatively, the pentavalent forms of MMA and DMA (MMA V , DMA V ) are the predominant arsenic methylated metabolites in urine, which are considered a tumor promoter and significantly associated with adverse health effects (Wang et al, 2013;Kuo et al, 2017). Meanwhile, the plasma arsenic metabolites are mainly present in a free state and make them distributed to different organs.…”
Section: Introductionmentioning
confidence: 99%